Air transport processes. Remuneration of pilots - A. V. Parkhimovich (Научный вестник МГТУ ГА, 2019)
Aviation is one of the leading industries in developed countries. The development of aviation is directly related to the strategic interests of any state. The development of market relations in this area presupposes the development and improvement of the methods of stimulating labor, the remuneration of employees of airlines, primarily of the flight crew. The airlines efficiency is largely dependent on the policies in the field of remuneration. Wages are an important incentive for the effective work of the airline, but at present the methods of remuneration of flight personnel in many companies do not fully meet present-day requirements. The article sets out major forms and systems of remuneration of flight personnel. Need to improve the wage system and to stimulate flight personnel has been emphasized. The author offers practical solutions to upgrade this system.